2012
DOI: 10.1136/amiajnl-2011-000185
|View full text |Cite
|
Sign up to set email alerts
|

A framework for evaluating the appropriateness of clinical decision support alerts and responses

Abstract: The new evaluation model offers a potentially effective method for assessing the clinical appropriateness of synchronous interruptive medication alerts prior to evaluating patient outcomes in a comparative trial. More work can determine the generalizability of the framework for use in other settings and other alert types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 32 publications
0
97
0
Order By: Relevance
“…Study data were collected as part of a quality improvement program with Institutional Review Board approval to improve drug safety (16). Briefly, the program featured CPOEbased clinical decision support (17,18), prospective monitoring, and as necessary, intervention by a clinical pharmacist through an electronic surveillance tool. Data for this observational study were collected at discharge by an independent outcome assessor.…”
Section: Settingmentioning
confidence: 99%
“…Study data were collected as part of a quality improvement program with Institutional Review Board approval to improve drug safety (16). Briefly, the program featured CPOEbased clinical decision support (17,18), prospective monitoring, and as necessary, intervention by a clinical pharmacist through an electronic surveillance tool. Data for this observational study were collected at discharge by an independent outcome assessor.…”
Section: Settingmentioning
confidence: 99%
“…In contrast to the results of a previous meta-analysis [4], this review found that decision support systems integrated into an electronic patient record or order entry interface were less likely to be effective than standalone systems [3]. A likely explanation for this finding is that these systems already had alerts and reminders in place at the time of the trial, and the users had developed "alert fatigue" --a habit of ignoring alerts and reminders brought about by repeated exposure [3], particularly to less relevant alerts [5]. A 2006 review found that 49% to 96% of alerts integrated into computerized order entry systems were ignored [6].…”
Section: Introductionmentioning
confidence: 82%
“…To do so might require a more in-depth assessment, possibly including medical chart reviews. McCoy et al 9 published a framework for evaluating alert appropriateness.…”
Section: Original Research and Contributionsmentioning
confidence: 99%